On the Market for Venture Capital - Jovanovic, Boyan; Szentes, Balázs (Journal of Political Economy, 2013)
We propose a theory of the market for venture capital that links the excess return to venture equity to the scarcity of venture capitalists (VCs). High returns make the VCs more selective and eager to terminate nonperforming ventures because they can move on to new ones. The scarcity of VCs enables them to internalize their social value, and the competitive equilibrium is socially optimal. Moreover, the bilaterally efficient contract is a simple equity contract. We estimate the model for the period 1989–2001 and compute the excess return to venture capital, which turns out to be 8.6 percent. Finally, we back out the return of solo entrepreneurs, which is increasing in their wealth and ranges between zero and 3.5 percent.